How the Rich Get Richer - Blair Fix (Economics from the Top Down, 2023)
The rich get richer. It's a phrase that packs a lot of punch. It's potent rhetoric, yet surprisingly accurate at describing how rising inequality plays out. Of course, there's nothing inevitable about the rich getting richer. We just happen to live in an age of growing corporate despotism. And our friends at Forbes have been there to document the disease. Forbes. Forbes who loves the free market. Forbes who loves obscene wealth. Forbes … the unwitting social scientist? When Malcolm Forbes started publishing his rich list — the Forbes 400 — back in 1982, he surely wasn't intending to do social science. By all accounts, Forbes simply loved opulence, and wanted to celebrate those who had the most of it. It was part of a 1980s trend that fetishized obscene fortunes. For the middle class, there was the saccharine show `Lifestyles of the Rich and Famous', which exalted the excesses of elite living. But for the upper class there was something less crass — a list that ignored the material trappings of wealth. It was called the Forbes 400, and it did nothing but report the raw numbers of capitalism — the capitalized wealth of the richest Americans. In hindsight, Malcolm Forbes' obsession with wealth seems ominous — kind of like the Sackler's claim that OxyContin wasn't addictive. But while Malcolm Forbes certainly cheerled the excesses of modern capitalism, he (and his magazine successors) also left an exquisite record of how US elites enriched themselves. Sure, the enrichment left a big mess. But for the moment, let's forget about cleaning it up and instead, investigate how it happened. Come, let's look at how the American rich got richer.
Keywords: P; P1; D3; G3; 330; billionaires; corporation; distribution; ownership